Probability theory : the logic of science - Jaynes, E. T. (Edwin T.); Bretthorst, G. Larry (Cambridge, UK ; New York, NY : Cambridge University Press, 2003)
A comprehensive introduction to the role of probability theory in general scientific endeavour. This book provides an original interpretation of probability theory, showing the subject to be an extension of logic, and presenting new results and applications. Ideal for scientists working in any area involving inference from incomplete information.
Includes bibliographical references (p. 705-720) and indexes.
oif 31/07/14, uaj 03/03/2015
Loan
Keywords: Probabilities; Mathematics -- Probability & Statistics -- General